Serum metabolomics reveals lipid metabolism variation between coronary artery disease and congestive heart failure: a pilot study. (June 2013) - Luan, Hemi; Chen, Xiaomin; Zhong, Shilong; Yuan, Xune; Meng, Nan; Zhang, Jianfeng; Fu, Jin; Xu, Ran; Lee, Connie; Song, Siyuan; Jiang, Hui; Xu, Xun
Abstract The aim of this pilot study is to find discriminating signals from the patient's congestive heart failure (HF) caused by coronary artery disease (CAD) through a non-target metabolomics method and test their usefulness in progress of human HF diseases. Multivariate data analysis was used to identify the discriminating signals. Interestingly, 12 metabolites contributing to the complete separation of HF from matched CAD were identified. Metabolic pathways including free fatty acids, sphingolipids and amino acid derivatives were found to be disturbed in HF patients compared with CAD patients. Lipid molecules associated with energy metabolism and signaling pathways may play key roles in the development of failing heart.